An energy aware resource allocation for cognitive radio OFDMA systems. (1st January 2014) - Chen, Xiaomao; Ouyang, Shan; Chen, Ziqiang
Multi-user orthogonal frequency division multiple access (OFDMA) network adaptive resource allocation is proposed. Subcarriers are assigned to each user in a way that ensures better spectrum efficiency; everyone is allocated power with quality of service (QoS) guarantees, while users' minimum rate requirements are met. Optimum transmit power of user is obtained by Lagrange method, validity of the time-share and corresponding hard mapping method are verified by simulation, the proposed algorithm can adapt allocate resource, minimising total transmit power.